2020
DOI: 10.1055/a-1186-1575
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Osteochondral Lesions of the Talus in Different Age Groups

Abstract: We analyzed the characteristics of 112 consecutive patients who were operatively treated for osteochondral lesions of the talus from August 2014 to April 2019 in our hospital. The patients were divided into three age groups: young-adult (<40 years), middle-age (40–60 years) and old-age (>60 years). The basic clinical features, localization and size of the lesions, Hepple stage, and surgical procedures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The efficacy of cerebellar tDCS in patients of different ages was also assessed using subgroup analysis. According to previous studies on stroke, someone aged less than 40 years was defined as a young adult, 40–60 years as middle-aged, and over 60 years as old-aged ( 19 , 20 ). Due to the small number of young-adult patients in this study ( n = 4), young-adult patients and middle-aged patients were combined into young-/middle-aged patients.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of cerebellar tDCS in patients of different ages was also assessed using subgroup analysis. According to previous studies on stroke, someone aged less than 40 years was defined as a young adult, 40–60 years as middle-aged, and over 60 years as old-aged ( 19 , 20 ). Due to the small number of young-adult patients in this study ( n = 4), young-adult patients and middle-aged patients were combined into young-/middle-aged patients.…”
Section: Resultsmentioning
confidence: 99%
“…Elias et al found that injuries located in the medial third were larger and deeper than those located elsewhere [ 3 ]. Cao et al noted that deeper-position cystic changes in the medial subchondral talus were typical of patients over 60 years of age with talar cartilage injuries [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elias et al found that the injury located in the medial 1/3 was larger and deeper [3]. Cao et al noted that deeper position cystic changes in the medial subchondral talus were typical of patients with talar cartilage injuries over 60 years of age [23].…”
Section: Discussionmentioning
confidence: 99%